Praanggapan dalam grup WhatsApp MBKM (Merdeka Belajar Kampus Merdeka) Universitas Dian Nuswantoro: Praanggapan dalam grup WhatsApp MBKM (Merdeka Belajar Kampus Merdeka) Universitas Dian Nuswantoro - Yusuf, Yusuf (Jurnal ABDI (Sosial, Budaya dan Sains), 2022)
This study aims to examine the use of presuppositions in conversations in the MBKM (Merdeka Belajar Kampus Merdeka) WhatsApp group at Dian Nuswantoro University. The type of research used is descriptive with a qualitative approach. The data source comes from the MBKM (Merdeka Belajar Kampus Merdeka) WhatsApp group at Dian Nuswantoro University. The type of research data is written data on conversations in the WhatsApp group for the period December 2021. The data collection technique used is export of conversations into Microsoft Word and literature study. The data analysis technique uses the Sudaryanto technique, namely data presentation, data analysis, and presentation of analysis results. The results showed that the most used presuppositions were lexical presuppositions with 7 utterances, followed by existential and structural presuppositions with 3 utterances, then 2 utterances of factive presuppositions, 1 utterance of non-factual presuppositions, and 0 utterance of counterfactual presupposition. Lexical presuppositions are mostly used because they are closely related to indirect speech acts that show a high level of politeness so that they can maintain harmonious relations in communication, while counterfactual presuppositions are not used because contradictory things are avoided to maintain conversational stability.